Cooperation of FGF/MEK/ERK and Wnt/β-catenin pathway regulators to promote the proliferation and pluripotency of mouse embryonic stem cells in serum- and feeder-free conditions - Tong Zhang; Huanyun Chen; Yiran Zhou; Wanghong Dong; Haibo Cai; Wen-Song Tan (Bioresources and Bioprocessing, 2019)
Abstract The FGF/MEK/ERK and Wnt/β-catenin signaling pathways have previously been proved to regulate mouse embryonic stem cell (mESCs) function. However, the relationships between these two pathways, especially their different functions on proliferation and pluripotency of mESCs, were rarely mentioned. Here, we investigated the effects of FGF/MEK/ERK and Wnt/β-catenin pathway regulators and their combinations on the proliferation and pluripotency of mESCs under serum- and feeder-free conditions. We found that MEK inhibitor PD0325901 and FGFR inhibitor SU5402 has paradoxical function on mESCs; one could promote proliferation along with differentiation and the other one could improve pluripotency while impairing cell proliferation. The combination of these two kinds of inhibitors could better regulate FGF/MEK/ERK pathway. Wnt/β-catenin pathway regulators SB216763 led to differentiation while promoting proliferation of mESCs. When we used FGF/MEK/ERK and Wnt/β-catenin pathway regulators in combination, the total expansion fold of mESCs reached 318.78 ± 47.95 and the proportion of SSEA-1-positive cells reached 82.40 ± 2.74% which were significantly higher than using the regulators alone. This finding indicates that regulators of FGF/MEK/ERK and Wnt/β-catenin pathways play different roles in the regulatory networks of mESCs. Their combination can better maintain the undifferentiated state and promote the proliferation of mESCs under serum- and feeder-free conditions.